Dynamic Coupling of Systemic and Intratumoral Estradiol in HER2-Positive and Triple-Negative Breast Cancer: A Validation Study of a Non-Invasive Surrogate - Nadhim Muhammad Askar; Widyanti Soewoto; Brian Wasita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The role of estradiol in the tumor microenvironment (TME) of estrogen receptor (ER)-negative breast cancers is increasingly recognized. Direct measurement of intratumoral estradiol is invasive, creating a barrier to clinical research. This study aimed to determine if circulating plasma estradiol can serve as a high-fidelity, non-invasive surrogate for intratumoral concentrations in HER2-positive (HER2+) and triple-negative breast cancer (TNBC). Methods: This retrospective, cross-sectional study included 60 women with primary operable HER2+ (n=21) and TNBC (n=39) who underwent mastectomy. Paired pre-operative plasma and post-operative tumor tissue samples were analyzed. Estradiol concentrations were quantified using a validated high-performance liquid chromatography-radioimmunoassay (HPLC-RIA) protocol. Clinicopathological data, including Body Mass Index (BMI), were collected. The primary outcome was the correlation between plasma and intratumoral estradiol, assessed by Spearman's rank correlation. Paired concentrations were compared using the Wilcoxon signed-rank test. Results: Baseline clinicopathological characteristics, including BMI, were well-balanced between the HER2+ and TNBC cohorts. A highly significant, strong positive correlation was found between plasma and intratumoral estradiol concentrations across the entire cohort (Spearman's ρ = 0.78, p < 0.001). This correlation remained robust in subgroup analyses of menopausal status and tumor grade. Interestingly, median intratumoral estradiol levels (30.0 pg/mL; IQR: 10.0-65.0) were significantly lower than paired median plasma levels (132.0 pg/mL; IQR: 40.0-225.0) (p < 0.001). Conclusion: Plasma estradiol demonstrates a strong and direct correlation with intratumoral estradiol in HER2+ and TNBC, validating its use as a reliable, non-invasive surrogate. This provides a crucial tool to explore the pathophysiology of the TME. The finding that intratumoral levels are lower than systemic circulation, yet tightly coupled, suggests a dynamic equilibrium that warrants further investigation into local estradiol metabolism and signaling in ER-negative disease.